THE ROLE OF INTERNAL CONTROL OVER SALES, RECEIVABLES, CASH RECEIPTS, AND CASH DISBURSEMENTS AT PT. INDAKO TRADING CO - Henny Andriyani Wirananda; Wan Dian Safina; Wilda Sri Munawaroh Harahap (UPMI Management, 2022)
This study aims to determine the role of internal control over sales, accounts receivable, cash receipts, and cash disbursements at PT. Indako Trading Co. The data used in this study is primary data, and the subject is PT. Indako Trading Co. While the object of this research is internal control. Data collection techniques were carried out through observation, interviews, and documentation studies. The overall research results indicate the role of internal control over sales at PT. Indako Trading Co has been running well because there is a separation of duties and authority between employees to minimize errors and fraud that might occur in the company. The role of internal control over receivables and sales at PT. Indako Trading Co is good and separates the parts according to their respective fields. Internal control over cash receipts and disbursements at PT. Indako Trading Co has not been carried out according to proper procedures. This is because employees in the inputting section of cash receipts sometimes often cover deposits from other people due to delays in recording cash. It is feared that fraud can occur regarding cash receipts and disbursements. JEL Classification: M20, M41, O16